Knowledge and behaviors of prevention of COVID-19 and the related factors in the rural population referred to the health centers: a cross-sectional study - Fatemeh Kordi; Nasrin Mokhtari Lakeh; Moluk Pouralizadeh; Saman Maroufizadeh (BMC, 2023)
Abstract Background and objective Observance of preventive behaviors is one of the main ways to break the coronavirus disease 2019 (COVID-19) chain of transmission. Therefore, the present study was conducted to determine the knowledge and behaviors of prevention of COVID-19 and the related factors in the rural population of Rasht city. Methods In this cross-sectional study, 344 people of the population referred to health centers in Rasht city were included through multi-stage cluster random sampling. The data were collected using a three-part researcher-made questionnaire including individual-social factors, knowledge about the prevention of COVID-19, and the preventive behaviors against COVID-19. Data analysis was performed using the Kolmogorov-Smirnov and Shapiro-Wilk tests, Spearman's correlation coefficient, and multiple logistic regression analysis, by SPSS software version 16 at a significance level < 0.05. Results The mean total score of knowledge about COVID-19 was at a moderate level, and the preventive behaviors of COVID-19 were at a good level. There was no significant relationship between the scores of awareness and preventive behaviors of COVID-19 (rs=0.001, P = 0.998). Awareness of COVID-19 was higher in university-educated individuals and women. Also, women, individuals who had access to the Internet, those trained by health centers, and those who were visited by health workers at home had more preventive behaviors. Conclusion Despite the lack of connection between knowledge and preventive behaviors, the villagers living in the suburbs of Rasht had a moderate level of knowledge and a good level of preventive behaviors of COVID-19. Appropriate educational interventions should be carried out to increase the awareness and performance of the rural residents.